Hydrogen bonding, spectroscopic (FT-IR and FT-Raman), UV−Vis, and Mulliken charge analysis of Guanosine-5′ -Diphosphate: insight from DFT and molecular docking - Chaudhary, Manoj Kumar; Chaudhary, Tarun; Joshi, Bhawani Datt; Verma, Gulab Singh; Shukla, Rajesh Kumar; Paneru, Tirth Raj (BIBECHANA, 2025)
Hybrid functional B3LYP has been used for quantum chemical calculation of Guanosine-5′ -Diphosphate (GDP) from DFT approach. The intra-molecular hydrogen bonding in the title molecule was rendered from Quantum theory of atoms in molecule (QTAIM). The vibrations of different functional groups of the GDP have been examined theoretically from FT-IR and FT-Raman calculation. The electrostatic potential surface revealed that the maximum positive potential is attributed to H4, and the highest negative potential corresponds to O31, predicting the sites for the intermolecular hydrogen bonding in the crystal packing of the title compound. The theoretical UV−Vis spectrum is used to calculate the excitation energy as well as excitation state of DGP. The binding affinity of GDP with Ras-related C3 botulinum toxin substrate 1 (RAC1) protein is calculated from molecular docking approach. The inhibition constant of 2P2L is less than that of 2H7V; hence, the title compound is a good inhibitor of 2P2L.